Karakteristik Organoleptik dan Nilai pH Yoghurt dengan Penambahan Sari Buah Mengkudu (Morinda citrifolia L) - Rasbawati, Rasbawati; Irmayani, Irmayani; Novieta, I. D.; Nurmiati, Nurmiati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
Yogurt is a processed product which is the fermentation of milk by lactic acid bacteria. The use of noni fruit in the process of making yogurt is one of the efforts to diversify food. This study aims to determine the effect of Morinda citrifolia L level extract on the characteristics and pH value of yogurt. The study used a completely randomized design (CRD) with 4 treatments (P0: 0%, P1: 5%; P2: 10% and P3: 15%) and the treatment was repeated 3 times. Observations were analyzed using variance analysis (ANOVA) and if there were significant differences, it would be followed by Duncan's Real Distance Difference test (Duncan's Multiple Range Test) to determine which treatment level gave a significant difference. The results showed that the addition of noni fruit extract had a very significant effect (P <0.01) on the organoleptic characteristics and pH value of yogurt. The best results obtained in this study were the addition of noni fruit extract with a level of 10%.